2012
DOI: 10.1109/tbme.2012.2194146
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Study of the Combined Thermoelectric Extracellular Stimulation of the Sciatic Nerve of the Xenopus Laevis: The Localized Transient Heat Block

Abstract: . A simulation study of the combined thermoelectric extracellular stimulation of the sciatic nerve of the Xenopus laevis: the localized transient heat block. IEEE Transactions on Biomedical Engineering, 59(6), pp. 1758 -1769 . doi: 10.1109 /TBME.2012 This is the accepted version of the paper.This version of the publication may differ from the final published version. 1  Abstract-This paper presents the response of the Xenopus laevis nerve fibers to combinations of electrical (cuff electrodes) and optical (inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 48 publications
(73 reference statements)
1
39
1
Order By: Relevance
“…We previously observed that increasing the infrared radiant exposure beyond a certain threshold will result in reversible inhibition of neural activity (17). Recent modeling studies demonstrated that this is due to non-uniform rate increases in the temperature-dependent Hodgkin-Huxley gating mechanisms (28). No inhibition was observed during this current study; however, reduction in evoked force with further increases in radiant exposure may occur.…”
Section: Discussionmentioning
confidence: 99%
“…We previously observed that increasing the infrared radiant exposure beyond a certain threshold will result in reversible inhibition of neural activity (17). Recent modeling studies demonstrated that this is due to non-uniform rate increases in the temperature-dependent Hodgkin-Huxley gating mechanisms (28). No inhibition was observed during this current study; however, reduction in evoked force with further increases in radiant exposure may occur.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that when high-frequency pulse trains are applied to a peripheral axon bundle, the amplitude and frequency can be tuned to induce a selective conduction block in certain fibers: relatively low stimulation rates selectively blocked activity in myelinated fibers while non-myelinated fibers were unaffected, while relatively high stimulation rates did the opposite – blocking activity in non-myelinated fibers while leaving myelinated fibers unaffected [34]. The mechanism through which the block occurs, as well as the reasons for its sensitivity to the rate of stimulation, both remain unknown, although theories involving activation and/or inactivation of several different ion channels have been proposed [35, 36]. Importantly, however, this work raises the possibility that HFS could selectively activate different types of neurons in the central nervous system as well.…”
Section: Introductionmentioning
confidence: 99%
“…Lines show the extracellular ( V e ) and membrane voltage ( V m = V i − V e , V i is intracellular voltage) at the nodes 1, 2, and 3 shown in (A) . For more details about the electrode-electrolyte model and the nerve model which is in this case Xenopus laevis sciatic nerve see Mou et al (2012). …”
Section: Biophysics Of Action Potential Generationmentioning
confidence: 99%
“…The plasma membrane electrical capacitance is reversibly affected by the temperature ( dC m / dT term) because the total capacitance of a lipid membrane in electrolyte solution includes in-series capacitance of ionic double layers at the interface between the (polar) membrane surface and electrolyte (Shapiro et al, 2012). Conversely during slow heating the changes to ionic channels dominate and in particular changes to Na + and K + activation/deactivation dynamics prevent action potential initiation and propagation (Mou et al, 2012; Duke et al, 2013). Thermal damage to tissue is a major issue with this method of neuromodulation, especially for suppression due to the higher temperatures and slower, more diffuse heating necessary (Wells et al, 2007).…”
Section: Neuromodulation Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation